2006
DOI: 10.1111/j.1444-2906.2006.01230.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oil droplet sizes of oil-in-water emulsion on the taste impressions of added tastants

Abstract: By conducing organoleptic analysis, the authors investigated the effect of oil droplet size on human preference to the taste of oil-in-water (o/w) emulsions to which several tastants were added. Two singly dispersed o/w emulsions, different in oil droplet sizes, consisting of 10% triacilglycerol purified from tuna, sardine or soybean oil, 0.5% emulsifier and water were prepared by ceramic membrane filtration. Organoleptic analysis showed that the impressions of sweetness, bitterness and umami, which were devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The bitterness of quinine in fish oil-in-water emulsions was only significantly dependent on droplet size for one of the fish oils studied, suggesting limited interaction with the droplet surface (140). On the other hand, in the same study rats significantly preferred the quinine-containing emulsions with smaller droplet sizes for all the three fish oils in a two-bottle preference test.…”
Section: Delivery Systems To Mask Bitter Tastementioning
confidence: 99%
“…The bitterness of quinine in fish oil-in-water emulsions was only significantly dependent on droplet size for one of the fish oils studied, suggesting limited interaction with the droplet surface (140). On the other hand, in the same study rats significantly preferred the quinine-containing emulsions with smaller droplet sizes for all the three fish oils in a two-bottle preference test.…”
Section: Delivery Systems To Mask Bitter Tastementioning
confidence: 99%
“…Figure 1 shows that the addition of a tastant to the emulsions did not affect their stability, and therefore, emulsions with and without tastant addition are considered stable and In addition to physicochemical stability, the emulsions' droplet size, viscosity and pH were measured to evaluate whether tastant addition affected these parameters in the emulsions. Previous results on the effects of droplet size on flavor detection have shown that taste perception was influenced in tastant-containing emulsions with droplet sizes varying between 1.0 and 5.5 mm (Nakaya et al 2006). Conversely, taste perception was not affected in unflavored emulsions with droplet sizes ranging from 0.5 to 6.0 mm ( These results suggest that the sensory results obtained in this research will not be affected by the physicochemical characteristics of the samples (stability, droplet size, viscosity and/or pH).…”
Section: Physicochemical Characterization Of the Emulsionsmentioning
confidence: 99%
“…Moreover, they concluded that lipids can limit the ability of tastants to arrive at and to interact with the taste receptor cells. Nakaya and others () found that bitterness intensities were lower in emulsion with smaller oil droplets.…”
Section: Resultsmentioning
confidence: 95%
“…Vingerhoeds and others () reported that emulsion droplet size did not have a significant effect on odor, taste, and aftertaste. In contrast, Nakaya and others () reported that bitter taste intensities of tuna oil emulsions with smaller droplet sizes (diameter = 1.00 μm) were lower than that of larger oil droplets (diameter = 5.50 μm). This supported the hypothesis that smaller oil droplets may have a bitterness suppressing effect.…”
Section: Introductionmentioning
confidence: 88%